Health and European Union. European Union and globalization - Zdunek, Kinga; Kulik, Teresa B.; Janiszewska, Mariola; Bogusz, Renata (Polish Journal of Public Health, 2011)
The development of public health theory is evolutionary in nature. It has reflected diff ff erent chronological eras which are influenced by their paradigms, research methods and preventive practices. Current developments in public health theory suggest that a f f ourth era has now emerged. The global burden of disease which is dominated by chronic non communicable diseases including mental disorders and injuries, global environmental changes and socioeconomic health determinants drive the new public health agenda. Strong leadership and coordination seem to be the most important factors influencing eff ff ectiveness of public health. Global health actors matter greatly in global health leadership. European Union attempts to strengthen the EU’s voice in global health.